ANALISIS KEMAMPUAN BERKOMUNIKASI SISWA KELAS IV DI SD BULUNGCANGKRING SELAMA PEMBELAJARAN DARING - dewi retno iswari; Deka Setiawan; Wafiq Nurul Huda (Jurnal Prasasti Ilmu, 2022)
Online/distance learning is a challenge for teachers to maximize the online learning process, and a challenge for students to understand the material and tasks given during online learning. In fact, in online learning activities, especially in Kudus.During online learning students are less communicative when learning is given via whatsapp. Students only see what whatsapp messages are conveyed by the teacher, so the teacher concludes that students already understand the material presented. The data collection technique was carried out by researchers by interviewing (interviewing), observation (observation), documents, and literature. Then perform data analysis. From the results of the study, it was found that 5 students could understand learning materials with good communication skills, 12 students were less able to understand subject matter with moderate communication skills and 18 students could not understand subject matter with low communication skills. lack of focus on listening to the material explained by the teacher, students' communication skills are low due to online learning, signals, there are some students who only fill attendance but do not follow the lesson, students do not do assignments optimally, students are less active during learning, there are some students who are constrained on data/quota packages, insufficient media from students, or device batteries running out during online learning and parents not supervising students while studying.Pembelajaran daring/jarak jauh menjadi tantangan tersendiri bagi guru untuk memaksimalkan proses pembelajaran secara daring, dan tantangan bagi siswa untuk mengerti materi dan tugas-tugas yang diberikan saat pembelajaran daringSelama pembelajaran daring siswa kurang komunikatif saat pembelajaran diberikan melalui whatsapp. Siswa hanya melihat apa pesan whatsapp yang disampaikan oleh guru,sehingga guru berkesimpulan siswa sudah paham akan materi yang disampaikan. Teknik pengumpulan data dilakukan peneliti dengan interview (wawancara), observasi (pengamatan), dokumen, dan kepustakaan. Kemudian melakukan analisis data. Dari hasil penelitian didapat bahwa 5 siswa dapat memahami materi pembelajaran dengan kemampuan komunikasi baik, 12 siswa kurang dapat memahami materi pelajaran dengan kemampuan komunikasi sedang dan 18 siswa tidak dapat memahami materi pelajaran dengan kemampuan komunikasi rendah.Faktor penghambat kemampuan berkomunikasi antara lain saat masa daring siswa kurang fokus mendengarakan materi yang dijelaskan oleh guru, Kemampuan komunikasi siswa rendah akibat pembelajaran daring, Sinyal, Terdapat beberapa siswa yang hanya mengisi presensi tetapi tidak mengikuti pembelajaran, Siswa tidak mengerjakan tugas secara maksimal, siswa kurang aktif saat pembelajaran berlangsung, Terdapat beberapa siswa yang terkendala pada paket data/kuota, Media yang kurang memadai dari siswa, atau baterai gawai habis saat pembelajaran daring dan orangtua kurang mengawasi siswa saat belajar